Identification of elite performance characteristics specific to anthropometric characteristics, athletic skills and motor competencies of combat athletes - Gürsoy, H.; Canli, U. (Baltic Journal of Health and Physical Activity, 2021)
Background: Knowing all the features required for elite performance in sports disciplines under the name of combat sports is among the most important parameters for discipline-specific talent identification and selection. Material and methods: The research group consists of male and female athletes within the age range of 12-17 who are licensed in taekwondo, karate, judo, and wrestling. A total of 70 athletes, 21 elite and 49 non-elite athletes, participated in the study voluntarily. Anthropometric, athletic and motor competency tests were applied to determine the elite performance elements of the groups. Results: Comparing the elite and non-elite athletes, statistically significant differences were found in favor of the elite group (p<0.05) in terms of height, sitting height, body weight, speed, core endurance, grip strength, upper extremity strength, anaerobic power, KTK jumping sideways and hopping. There was no statistical difference between the groups in terms of fat percentage, BMI, agility, vertical jump, flexibility, KTK moving sideways and walking backwards values (p>0.05). Conclusions: There seem to be important distinctions between athletes who reach the national peak and those who do not, in terms of height, sitting height, body weight, speed, anaerobic power, grip strength, upper extremity and core strength, as well as motor competency related to anaerobic power.